ESTABLISHMENT OF OIL DISPERSED SYSTEMS BY THE PARAMAGNETIC PROBE AND FREE RADICALS - Bukanova A.S.; Kairlieva F.B.; Sakipova L.B.; Karabasova N.A.; Bukanova С.K.; Nasirov R.N. (Academic Scientific Journal of Chemistry, 2019)
We managed to establish experimentally existence of disperse particles of resinous asphaltene substance (RAS) in crude oil.The EPR spectra of nitroxyl in the oils of the Caspian region were studied, and as it can be seen, the component mz=-1 splits into two lines.Heating up to 100 °C leads to disappearance extreme components which after cooling of a sample to room temperature appears only after long upholding (not less than 2 h).This phenomenon is connected with heterogeneity of oil, that is with existence in it of considerable number the asfaltenosmolistykh of particles.This phenomenon is associated with the heterogeneity of oil, that is, with the presence in it of a significant number of resin-asphaltenic particles. At low concentrations of RAS in oil, they are molecular dispersed and the molecules of the dissolved RAS freely move in the oil independently of each other.With a significant content of RAS in the oil micelles are formed. Particles of nitroxyl radicals are adsorbed on RAS micelles. Non-adsorbed particles of nitroxyl radicals chaotically move in the dispersive environment of oil. Two such different conditions of the nitroxyl radical in oil are in thermodynamic balance. In low viscosity oils (Tengiz) where RAS is molecularly dispersed, particles of dissolved nitroxyl radicals move freely, and in the EPR spectrum we can observe three lines of them with the same intensities.